The Comparison in Indoor and Outdoor Physical Activity of Locomotor Skill programs in Preschool - Nisa, Luthfatun; Naser Ali Abdulghani; Jamaluddin Shiddiq (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aimed to determine how the effect of structured movement session in natural outdoor on the gross motor skill of children, especially activities in the natural outdoor. The focus of the discussion in this study were revealed and analyzed the locomotor skills in children 5 to 6 years old of preschool, and compared of indoor structured play and natural outdoor free play on the locomotor skill of preschool children. The subjects were 2 schools with indoor structured play and another school with natural outdoor free play. Sixty children (35 boys and 25 girls) served as subjects. Data obtained through observation, documentation and then the pefomance a chi-square test was used to data analyze, to determine the difference in a locomotor skill between in an indoor structured play and natural outdoor free play of preschool children. The results of this study showed that there is no significant difference between the locomotor skills of children in indoor structured play or outdoor free play. A t-test score for independent sample was not significant (-2.182 < 0.05)(t = -2.182, df = 58, p = .86), its mean there was no difference in a locomotor skill between in a indoor structured play and natural outdoor free play. This allows for consideration for parents, practitioners, and academics in delivering stimulation and gross motor activities on children.